Prophylaxis against systemic infection after transrectal biopsy for suspected prostatic carcinoma. - Ashby, E C (1978)
Five minutes after transrectal prostatic biopsy 16 out of 21 patients were shown by blood culture to have bacteraemia. Antibiotic prophylaxis--routinely with ampicillin and metronidazole for 48 hours--prevented progression to septicaemia, and four days after the procedure all blood samples were negative. Irrespective of whether antibiotic prophylaxis is used, blood culture should be routine in all patients undergoing transrectal prostatic biopsy.